Institucija figure i figura institucije u povijesnoznanstvenoj praksi - Ivić, Nenad (Array, 1998)
This paper discusses social and theoretical implications of Hayden Whites figural interpretation of historiographical discourse. Theoretical implications are developped following Dominic LaCapras criticsm; social implications are worked out following Michel de Certeau. Figural interpretation is shown to be embedded in the social context of historiographical practice.